Multicolour fluorescent carbon nanoparticle probes for live cell imaging and dual palladium and mercury sensors. Issue 14 (21st March 2016) - Sharma, Vinay; Saini, Anoop Kumar; Mobin, Shaikh M.
Abstract : Cytocompatible carbon nanoparticles (CNPs) having high quantum yield and multicolour bioimaging properties were synthesized and employed as sensitive, selective and rapid dual sensor for Pd 2+ and Hg 2+ . Abstract : Carbon based nanomaterials are emerging as a desirable alternative to semiconducting quantum dots due to their unique optical properties and biocompatibility. The present study demonstrates the design and synthesis of highly fluorescent carbon nanoparticles (CNPs). The CNPs are investigated for their biocompatibility and henceforth successfully employed as promising multicolor bioimaging probes in A375 and DU145 cell lines. Furthermore, a "turn off" mode has been established for the detection of noble metal palladium (Pd 2+ ) and heavy metal mercury (Hg 2+ ) by quenching the fluorescence of CNPs. The CNP sensor responded to the detection of Pd 2+ (5–100 μM) and Hg 2+ (1–18 μM) in a wide range with the limit of detection (LOD) of 58 nM for Pd 2+ and 100 nM for Hg 2+ . The CNP sensor was employed for the detection of Pd 2+ and Hg 2+ in real water samples and detection of leftover palladium catalysts in a model reaction system. Also, the CNPs were successfully employed as intracellular mercury and palladium sensors using confocal microscopy.